Reflecting on 21 Years of the HILDA Survey - Evans, Ann (My University, 2021)
In 2022, the Household, Income and Labour Dynamics in Australia (HILDA) Survey will field its 21st annual wave of data collection; a milestone that cannot pass without celebration. This issue of the Australian Economic Review celebrates the contribution to informed public discourse, policy analysis and development and understanding of life in Australia that the HILDA Survey has enabled.
The Australian Economic Review
Keywords: Surveys and survey methodology